Seroprevalence and Risk Factors of Syphilis with HIV Co-Infection at Mangusada General Hospital Badung, Bali - Ni Putu Eka Kristi Permatasari; Tjokorda Istri Amrita Rosvanti; Anak Agung Ari Agung Kayika Silayukti; Anak Agung Istri Saraswati Dewi; Made Hemina Laksmi (The International Journal of Medical Science and Health Research, 2025)
Background: Syphilis and HIV are diseases transmitted through sexual contact, which makes co-infection of these two diseases highly probable. Research in several countries reports that syphilis infection can increase 3-5 times the risk of HIV transmission. This study aims to determine the seroprevalence and risk factors of syphilis patients with HIV co-infection. Methods: This was a retrospective descriptive study based on the medical records of new syphilis patients with HIV co-infection who presented to the Dermatology and Venereology Outpatient Clinic in Mangusada Hospital, Badung, Bali from May 2022 to May 2025. The data collected included the number of patients, time of visit, gender, patient's age at first diagnosis of syphilis, marital status, education, occupation, ethnicity, sexual orientation, clinical symptoms, physical examination of skin or genital lesions, stage, CD4 count, and serological/VDRL testing. Data were analyzed with SPSS version 24. Results: Based on 26 subjects in this study, the majority were male 21 (80.8%). Fifteen of these had a homosexual orientation (MSM). The highest age group was the 20-29 year range, with 11 individuals (42.4%), predominantly with an unmarried or divorced status at 61.5%. The highest level of education was high school, accounting for 57.7%, with a predominance of private sector employees at 46.2%. The Balinese ethnicity showed the highest number at 57.7%, and the stage of syphilis was dominated by late latent syphilis at 50%. The largest proportion of subjects had a CD4 count of <200 cells/mm³ (65.4%), and the most common VDRL result was 1:128 (30.8%). Conclusion: Syphilis and HIV infections are interconnected. The results of this study show a predominance of male subjects with a homosexual orientation who are in the late latent stage of syphilis.